The Multiple Modernities of Sweden - Janina Gosseye (Footprint)
This article reviews the book Swedish Modernism. Architecture, Consumption and the Welfare State, edited by Helena Mattsson and Sven-Olov Wallenstein. In this volume, the editors plea for the construction of ‘multiple modernities’, following which a more diversified understanding of the European welfare state can be constructed.